A CASE OF Tn-POLYAGGLUTINATION WITH PANCYTOPENIA - Tsujibayashi, Mitsuyo; Iwanaga, Takauki; Senoo, Taiko; Okubo, Yasuto; Fujita, Michiko; Akiyama, Mitsuko; Horiuchi, Atsushi; Fujikawa, Yoko; Kanemitsu, Yasushi; Ashida, Takashi (Journal of the Japan Society of Blood Transfusion, 1984)
Polyagglutination of erythrocytes is observed when most normal ABO-compatible human serum agglutinate the tested red cells. Recently we had a case of polyagglutination caused by the Tn antigen. Tn-polyagglutination was detected in the blood of a 78-years-old female patient with pancytopenia. The true blood group of the patient was O, but her cells had an aquired A-like specificity. Confirmation that the polyagglutination was caused by Tn activation was established by the reaction of lectins, weak aggregation with polybrene, and low sialic acid levels of red cell. This change of red cell membrane was thought to be due to somatic mutation at stem cell level.